Responding to the tragedy of military training-related death - Loo, Bernard Fook Weng (2016)
Fatalities as a result of military training is always regrettable. If the armed forces is to be credible and effective in war, military training has to tough and realistic. It means that fatalities as a result of military training may be unavoidable. Nevertheless, in a peacetime armed forces, it is important to remember that these fatalities still represent the ultimate sacrifice that a citizen-soldier, and his family that survives him, makes. The country therefore has to be demonstrably sorrowful and grateful for this sacrifice.